(untitled) (Вестник КазНУ. Серия Востоковедения, 2017)
Japanese national identity have been changed under the influence of other countries. The crises, that have occurred in the country, threatened the traditional identity of the Japanese people. Especially actively started to study identity in the postwar years. At this time, developed classical literature. It became popular to write real and negative aspects of post-war lives of ordinary Japanese people. Many writers of the time such as Kenzaburo Oe, Shintaro Ishihara, Yamakawa Macao, Yukio Mishima, showed in his works psychological changes a person, his experience of the defeat in the war, its goals and assessment of what is happening around. This article describes the most bright works in which you can find reflection of the Japanese after war social life and understanding the identity of Japanese writers.